GAYA KEPEMIMPINAN CAMAT DALAM PENYELENGGARAN PEMERINTAHAN DI KECAMATAN SUNGAI AMBAWANG KABUPATEN KUBURAYA - AYU WIDOWATI JOHANNES (Jurnal Ilmu Pemerintahan Suara Khatulistiwa, 2018)
The performance of the apparatus in carrying out government duties is expected to be carried out seriously by having a willingness to compete giving the best in order to achieve the stated goals. The function of guidance and direction of a sub-district head is reflected in the leadership style that is applied to the administration of government, development and community empowerment. The results of the study show that the Cooperation dimension, the dimension of listening and receiving suggestions / inputs and the dimensions of encouraging decision-making, are more dominantly applied by the sub-district head, which is the dimension of the participative leadership style.